THE IMPACT OF SERVANT LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MEDIATED BY SATISFACTION WORK ON EMPLOYEES OF THE PALM OIL RESEARCH CENTER - Ardiani, Winda; Sunaryo, Sunaryo; Azzahra, Amanda (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
This study is a causal study with a quantitative approach. This study was conducted at the Medan Palm Oil Research Center (PPKS) with a population that became a saturated sample of 150 employees at the Medan City Palm Oil Research Center. The results of this study indicate that servant leadership has a positive and significant influence on OCB in employees of the Palm Oil Research Center. Servant leadership has a positive and significant influence on job satisfaction in employees of the Palm Oil Research Center. Job satisfaction does not affect OCB in employees of the Palm Oil Research Center. And servant leadership does not affect OCB through job satisfaction of employees at the Palm Oil Research Center